2018
DOI: 10.1080/00332747.2017.1402569
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Social Support and PTSD Treatment Response During Prolonged Exposure

Abstract: These findings suggest that social support and PTSD symptoms are related throughout treatment. Social support moderated the change in PTSD symptoms, whereas PTSD symptoms did not moderate changes in social support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
50
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 46 publications
7
50
1
1
Order By: Relevance
“…At the symptom level, more contact predicted less severe flashbacks, behavioural avoidance, loss of interest, estrangement, and numbing. These findings build on those of a previous study of the association between PTSD and social support conducted in a small sample of veterans who had completed residential PTSD treatment (Laffaye et al, 2008), and complement results found in active-duty service members (Shallcross et al, 2016), outpatients with PTSD (Price et al, 2018), and MVA survivors (LeBlanc et al, 2016).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…At the symptom level, more contact predicted less severe flashbacks, behavioural avoidance, loss of interest, estrangement, and numbing. These findings build on those of a previous study of the association between PTSD and social support conducted in a small sample of veterans who had completed residential PTSD treatment (Laffaye et al, 2008), and complement results found in active-duty service members (Shallcross et al, 2016), outpatients with PTSD (Price et al, 2018), and MVA survivors (LeBlanc et al, 2016).…”
Section: Discussionsupporting
confidence: 84%
“…This premise is supported by previous research showing that family support for treatment increases veterans' likelihood of staying in treatment (Meis et al, 2019) and that veterans with more social support were less likely to endorse the belief that it is up to them to handle their problems and more likely to seek treatment (Graziano & Elbogen, 2017). Further, family involvement in PTSD care was associated with more PTSD symptom reduction (Laws, Glynn, McCutcheon, Schmitz, & Hoff, 2017), and greater social support predicts better PTSD treatment response (Price, Gros, Strachan, Ruggiero, & Acierno, 2013;Price et al, 2018;Shnaider, Sijercic, Wanklyn, Suvak, & Monson, 2017). Notably, in line with the social causation model, Price et al (2018) also found that social support moderated PTSD outcome but that PTSD did not moderate increases in social support during treatment.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Treatments are combined due to the lack of group differences. received PE, a higher level of social support over the course of treatment was related to larger reductions in PTSD symptom severity (Price et al, 2018). In the current study, PE was more efficient at reducing fear of intimacy and negative cognitions in social situations.…”
Section: Discussionmentioning
confidence: 99%
“…The authors questioned if perceived social support can be increased by therapy and stated that more research is needed in this field. In another examination, a positive association was found between social support during therapy and reduction of PTSD symptoms, as well as an increase in social support (34).…”
Section: Introductionmentioning
confidence: 99%